2019
DOI: 10.3390/nano9010052
|View full text |Cite
|
Sign up to set email alerts
|

New Polymers for Needleless Electrospinning from Low-Toxic Solvents

Abstract: Electrospinning is a new technology whose scope is gradually being developed. For this reason, the number of known polymer–solvent combinations for electrospinning is still very low despite the enormous variety of substances that are potentially available. In particular, electrospinning from low-toxic solvents, such as the use of dimethyl sulfoxide (DMSO) in medical technology, is rare in the relevant scientific literature. Therefore, we present in this work a series of new polymers that are applicable for ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…Several solvents which are oft en used in electrospinning, however, are toxic or corrosive. While a large number of biopolymers can be electrospun from water [6,7], only few waterresistant polymers can be spun from low-toxic solvents such as dimethyl sulfoxide (DMSO) [8]. Th is is one of the reasons why polyacrylonitrile (PAN) is of large interest in electrospinning, apart from its usability as a precursor for carbon nanofi bres [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Several solvents which are oft en used in electrospinning, however, are toxic or corrosive. While a large number of biopolymers can be electrospun from water [6,7], only few waterresistant polymers can be spun from low-toxic solvents such as dimethyl sulfoxide (DMSO) [8]. Th is is one of the reasons why polyacrylonitrile (PAN) is of large interest in electrospinning, apart from its usability as a precursor for carbon nanofi bres [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…According to the electrospinning raw materials, it can be divided into melt electrospinning [46][47][48], solution electrospinning [49,50] and mixed electrospinning [51][52][53]. According to the design of the spray head, it can be classified as needleless electrospinning [54][55][56], coaxial or triaxial electrospinning [57][58][59][60][61][62], multi-jet electrospinning [63][64][65], etc. The application of electrospinning technology will be described below according to different situations.…”
Section: Strategies For the Preparation Of Functional Electrospun Matmentioning
confidence: 99%
“…Frequence (%) MBE MFSE OSFSE SSFSE 4.0×10 5 ˂ ER ≤ 4.4×10 5 0.00 0.00 24.88 0.00 4.4×10 5 ˂ ER ≤ 4.8×10 5 0.00 0.00 21.39 0.00 4.8×10 5 ˂ ER ≤ 5.2×10 5 23.88 0.00 9.95 0.00 5.2×10 5 ˂ ER ≤ 5.6×10 5 31.84 0.00 5.97 0.00 5.6×10 5 ˂ ER ≤ 6.0×10 5 16.42 69.11 3.48 0.00 6.0×10 5 ˂ ER ≤ 6.4×10 5 4.98 10.99 2.49 51.67 6.4×10 5 ˂ ER ≤ 6.8×10 5 2.99 5.24 1.99 10.00 6.8×10 5 ˂ ER ≤ 7.2×10 5 2.49 2.62 1.99 6.67 7.2×10 5 ˂ ER ≤ 7.6×10 5 1.99 2.62 1.00 5.55 7.6×10 5 ˂ ER ≤ 8.0×10 5 1.49 1.57 1.00 5.00 8.0×10 5 ˂ ER ≤ 8.4×10 5 1.49 1.05 1.00 4.44 8.4×10 5 ˂ ER ≤ 8.8×10 5 1.00 2.09 0.50 2.78 8.8×10 5 ˂ ER ≤ 9.2×10 5 1.00 0.52 1.00 1.67 9.2×10 5 ˂ ER ≤ 9.6×10 5 0.00 1.05 0.50 2.78 9.6×10 5 ˂ ER ≤ 1.0×10 6 1.00 0.52 0.50 2.22 1.0×10 6 Fig.9 and Table 3, it could be found that the f-value of the MBE device was the largest, and the f-value of the MFSE device was the smallest. That meant the electric field distribution of the MBE device was the most non-uniform due to the influence of the polymer nozzle, which caused the multiple jets generated mainly on the top of the bubble produced by the nozzle and near the top edge of the copper reservoir, as shown in Fig.3(a).…”
Section: Er (V/m)mentioning
confidence: 99%
“…Due to their excellent properties, such as high surface-to-volume ratios and high porosities, nanomaterials have become more and more important in industrial manufacturing. As one of the most important methods for preparing nanomaterials, electrospinning (ES) [1][2][3] has been receiving much attention [4][5][6][7]. But with the advancement of nanotechnology and the increasing performance requirements of nanomaterials, the fatal shortcoming of the traditional ES process, low yield [8,9], has received more attention.…”
Section: Introductionmentioning
confidence: 99%